Adult neurogenesis in the mouse dentate gyrus protects the hippocampus from neuronal injury following severe seizures. Issue 8 (23rd January 2019) - Jain, Swati; LaFrancois, John J.; Botterill, Justin J.; Alcantara‐Gonzalez, David; Scharfman, Helen E.
Abstract: Previous studies suggest that reducing the numbers of adult‐born neurons in the dentate gyrus (DG) of the mouse increases susceptibility to severe continuous seizures (status epilepticus; SE) evoked by systemic injection of the convulsant kainic acid (KA). However, it was not clear if the results would be the same for other ways to induce seizures, or if SE‐induced damage would be affected. Therefore, we used pilocarpine, which induces seizures by a different mechanism than KA. Also, we quantified hippocampal damage after SE. In addition, we used both loss‐of‐function and gain‐of‐function methods in adult mice. We hypothesized that after loss‐of‐function, mice would be more susceptible to pilocarpine‐induced SE and SE‐associated hippocampal damage, and after gain‐of‐function, mice would be more protected from SE and hippocampal damage after SE. For loss‐of‐function, adult neurogenesis was suppressed by pharmacogenetic deletion of dividing radial glial precursors. For gain‐of‐function, adult neurogenesis was increased by conditional deletion of pro‐apoptotic gene Bax in Nestin‐expressing progenitors. Fluoro‐Jade C (FJ‐C) was used to quantify neuronal injury and video‐electroencephalography (video‐EEG) was used to quantify SE. Pilocarpine‐induced SE was longer in mice with reduced adult neurogenesis, SE had more power and neuronal damage was greater. Conversely, mice with increased adult‐born neurons had shorter SE, SE had less power, and there was less neuronal damage. The results suggest that adult‐born neurons exert protective effects against SE and SE‐induced neuronal injury.